MODELS OF IMPROVING READING SKILLS IN MODERN PEDAGOGY (The Conference Hub, 2025)
The requirements for learning and teaching English are changing every hour. Explaining the most important elements of language learning in a correct and easy way requires high pedagogical skills from the teacher. The most basic foundation of learning English is reading skills. This article extensively discusses models for improving reading skills.